Association of intraprocedural near admission-level blood pressure with functional outcome in stroke patients treated with mechanical thrombectomy - Min Chen; Lukas Daniel Sauer; Mika Herwig; Jessica Jesser; Meinhard Kieser; Arne Potreck; Markus Möhlenbruch; Peter Arthur Ringleb; Silvia Schönenberger (Neurological Research and Practice)
Abstract Background Optimal blood pressure management during endovascular stroke treatment is not certain. We hypothesized that time or proportion of intraprocedural systolic blood pressure spent in a range around admission blood pressure might be associated with better clinical outcome. Methods We conducted a retrospective observational study at a single center at a university hospital, which included patients from August 2018 to September 2020 suffering from acute ischemic stroke with anterior circulation vessel occlusion and treated with endovascular therapy. Time and proportion of procedure time where systolic blood pressure (SBP) was near the baseline SBP on admission (bSBP) were used as exposure variables. The primary outcome was the occurrence of mRS score 0–2 three months after stroke. The primary analysis was performed by fitting a logistic regression model adjusted for baseline NIHSS, pre-stroke mRS, mTICI score, intubation, age and sex. Results We included 589 patients in the analysis. Mean (SD) age was 76 (12) years, 315 were women (53%) and mean (SD) NIHSS score at admission was 15 (7.5). Mean (SD) bSBP was 167 (28) mmHg and mean (SD) intraprocedural SBP was 147 (21) mmHg. The proportion of time where intraprocedural SBP was in range of bSBP ± 20% was associated with a slightly higher odds of achieving favorable outcome (adjusted OR, 1.007; 95% CI, 1.0003–1.013). Conclusion A higher proportion of intraprocedural time with systolic blood pressure in range of ± 20% of the admission level is associated with higher odds of favorable functional outcome. Trial Registration Not applicable.